Bedside provocation and liberation maneuvers in patients with benign paroxysmal positional vertigo. Issue 1 (24th February 2020) - Straumann, Dominik; Brandt, Thomas
In the majority of cases, benign paroxysmal positional vertigo (BPPV) originates from the posterior or horizontal semicircular canals. If performed correctly, the maneuvers that diagnose or treat canalolithiasis or cupulolithiasis are highly effective. This article describes the provocation (i.e. diagnostic) and liberation (i.e. therapeutic) maneuvers to be applied in patients with BPPV. The step-by-step descriptions of the maneuvers are supplemented by practical recommendations.